Planning and designing libraries for children and young people - Dewe, Michael (London : Library Association Pub., 1995)
The publication will enable school and children's librarians to develop a critical and evaluative attitude to the utilization, layout, appearance and environment of their libraries.
Includes bibliographical references (p. 211-220) and index.
uaj 19/09/2014
Loan
Keywords: Library architecture -- Great Britain; Children's libraries -- Great Britain -- Planning